1995
DOI: 10.1128/aac.39.2.476
|View full text |Cite
|
Sign up to set email alerts
|

CP-115,953 stimulates cytokine production by lymphocytes

Abstract: The cytotoxic quinolone CP-115,953 specifically exerts its inhibitory effect upon eukaryotic topoisomerase II. CP-115,953 stimulates DNA cleavage mediated by topoisomerase II with a potency approximately 600 times greater than that of ciprofloxacin, a quinolone antibacterial agent that currently is in clinical use. Because ciprofloxacin has been reported to strongly enhance interleukin-2 production, we considered it important to study the effect of CP-115,953 on interleukin-2 and gamma interferon (IFN-␥) mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The observed low levels of T cells and cytokines associated with the presence of antibiotics seem to adjust to the previously mentioned feedback pattern. Thus, low levels of T lymphocytes can secrete low levels of cytokines and chemotactic molecules which may be low enough to contribute to their feedback participation promoting the presence of T lymphocytes (Jiménez-Valera et al 1995;Riesbeck & Forsgren 1995;Campello et al 2006).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…The observed low levels of T cells and cytokines associated with the presence of antibiotics seem to adjust to the previously mentioned feedback pattern. Thus, low levels of T lymphocytes can secrete low levels of cytokines and chemotactic molecules which may be low enough to contribute to their feedback participation promoting the presence of T lymphocytes (Jiménez-Valera et al 1995;Riesbeck & Forsgren 1995;Campello et al 2006).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…During the course of infection, cytokines have been recognised as capable of modifying cell activities. IL-8, IL-1␤, TNF-␣ and IL-6, which have a broad spectrum of activity on cells involved in immune and inflammatory reactions [10], could help to mediate resistance to bacterial pathogens. For example, IL-1␤ and TNF-␣ induce the adherence of PMNs, lymphocytes and monocytes to the endothelial cells and limit infection allowing the passage of these cells into the inflammatory sites [10].…”
Section: Discussionmentioning
confidence: 99%
“…IL-8, IL-1␤, TNF-␣ and IL-6, which have a broad spectrum of activity on cells involved in immune and inflammatory reactions [10], could help to mediate resistance to bacterial pathogens. For example, IL-1␤ and TNF-␣ induce the adherence of PMNs, lymphocytes and monocytes to the endothelial cells and limit infection allowing the passage of these cells into the inflammatory sites [10]. Recent investigations have shown that some antibiotics, in addition to their antimicrobial effects, can interfere with cytokine production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations